Tapia's Syndrome after Cosmetic Malar Augmentation: a Case Report - Farhad Ghorbani; Saeid Tavanafar; Hamidreza Eftekharian (Shiraz University of Medical Sciences, 2019)
Tapia's syndrome is an infrequent complication of airway manipulation. It is usually due to an extra-cranial ipsilateral injury to the hypoglossal nerve and the recurrent laryngeal branch of the vagal nerve, which can happen after any surgery. It is usually characterized by unilateral paralysis of the muscle of the tongue and vocal cords although it can also occur bilaterally. We present a patient with postoperative unilateral hypoglossal and recurrent laryngeal nerves palsy that occurred after cosmetic malar augmentation for esthetic correction of the left cheek flatness with an uncomplicated transnasal intubation. We report the first case of Tapia's syndrome after porous polyethylene implantation for cosmetic cheek reconstruction. The patient was treated immediately after the diagnosis with 0.5mg dexamethasone for two weeks. After three months, the movements of the vocal cord and tongue movement started to improve and the patient's hoarseness fully recovered after six months.